Agricultural cooperatives in Ethiopia: Results of 2012 ATA Baseline Survey - Bernard, Tanguy; Abate, Gashaw T.; Lemma, Solomon (International Food Policy Research Institute, 2013)
Since 1994, the Government of Ethiopia has made efforts to promote a new generation of cooperatives that differ from their predecessors that were put in place under previous regimes. These new types of cooperative should be (1) based on the members’ “free will to organize”; (2) able to fully participate in the free market; and (3) free of government intervention in their internal affairs (Proclamation 85/1994). In agriculture, cooperatives are meant to play a central role in efforts to develop the sector. For example, Ethiopia’s Sustainable Development and Poverty Reduction Program (FDRE 2002, 43) seeks “to organize, strengthen and diversify autonomous cooperatives to provide better marketing services and serve as a bridge between small farmers (peasants) and the non-peasant private sector.”